Elderly population changes in small- and medium-sized cities in China, 1982–2000. (April 2018) - Gan, Yiqing; Fong, Eric
China has been experiencing large-scale internal migration since the 1980s. Existing research studies have paid great attention to the migrant's adaptation process in large cities and the issue of left-behind children in rural areas, while the demographic consequences of internal migration to small- and medium-sized cities have been surprisingly omitted. Our study takes the initial step of exploring elderly representation changes in small- and medium-sized cities from 1982 to 2000. We derived elderly representation changes in cities in six provinces both in 1982–1990 and 1990–2000 from censuses, and examined how a city's total population size, distance from large cities and gross domestic product performance relate to its elderly representation. Findings show that smaller cities with better economic performance that are closer to large national cities are more prone to age rapidly. This association only applies to the 1990–2000 period. Implications of these findings are discussed.